Hubungan Perilaku Prososial dan Interaksi Teman Sebaya dengan Minat Belajar Siswa - Jeane Agustientje Frans; Hasanuddin Hasanuddin; Suaidah Lubis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine whether there is a relationship between prosocial attitudes and peer interaction with the learning interest of the Medan Gereja Protestan Indonesia Barat (GPIB) Catechization students in 2020/2021. The research method is a quantitative descriptive correlative type with a correlative study pattern by placing the research variables in two groups, namely the independent variable and the dependent variable. The research population is the Medan GPIB Catechization students in 2020/2021. The sampling technique used was Proportional Random Sampling with a selected sample size of 100 people, the data collection method used prosocial attitude instruments, peer interaction instruments, and students' interest in learning instruments. Analysis of research data shows that (1) the relationship between prosocial attitudes and student interest in learning is indicated by the coefficient rx1y = 0.557 and p = 0.000 with p <0.05; (2) the relationship between peer interaction and student interest in learning is shown by the coefficient rx2y = 0.628 and p = 0.000 with p <0.05; (3) the relationship between prosocial attitudes and peer interaction with student interest in learning is shown by the coefficient coefficient F = 44.166 and R (regression coefficient) = 0.557 while R2 = 0.311 with p = 0.000 (p < 0.01).